2019
DOI: 10.5603/fm.a2018.0070
|View full text |Cite
|
Sign up to set email alerts
|

Combination of vitamin E and L-carnitine is superior in protection against isoproterenol-induced cardiac injury: histopathological evidence

Abstract: Background: L-carnitine and Vitamin E have antioxidant properties. This study aimed to assess

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…In another rat study of ALCAR, the agent reduced cardiac interfiber bleeding and cardiac fiber atrophy. 19 Altun et al 20 observed that combined treatment with ALCAR and CDDP decreased autotoxic effects by approximately 22%. Handzlik et al 21 found that ALCAR decreased these effects by 59% under acute hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In another rat study of ALCAR, the agent reduced cardiac interfiber bleeding and cardiac fiber atrophy. 19 Altun et al 20 observed that combined treatment with ALCAR and CDDP decreased autotoxic effects by approximately 22%. Handzlik et al 21 found that ALCAR decreased these effects by 59% under acute hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than attempting to modify one nutrient at a time, the diet tested in this study contained a cocktail of multiple supplemental nutrients (Table 1). Previous studies have shown that combinations of nutrients can perform better than single nutrient supplements [38, 39]. A blinded, randomized placebo-controlled interventional study was conducted, using echocardiogram evaluation as the primary endpoint, to evaluate the effect of the diet on progression of early stage MMVD in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…ISO group showed significantly elevated cTnI, LDH and CKMB compared to the control which matches numerous former studies [1,[22][23][24][25][26] . This marked increase in serum level of cardiac enzymes denotes necrotic damage and leakiness of myocardial cell membrane [23,27] and could be explained by the enhanced production of free radicals with subsequent lysosomal degradation and alteration of myocardial structure as well as function [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The edema was manifested in this work by the wide separations between myofibers and may explain the significant increase in the ventricular diameter and HWI detected in ISO group. Furthermore, it was proved that ISO administration in rats resulted in dilated congested or ruptured capillaries with hemorrhagic foci between the fibers followed by perivascular inflammatory cells [28] .…”
Section: One Of the Major Regulators Of Autophagy Is Ampk;mentioning
confidence: 99%